2012
DOI: 10.1136/acupmed-2012-010167
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Combined with Curcumin Disrupts Platelet-Derived Growth Factor β Receptor/Extracellular Signal-Regulated Kinase Signalling and Stimulates Extracellular Matrix Degradation in Carbon Tetrachloride-Induced Hepatic Fibrosis in Rats

Abstract: Background Acupuncture treatment has been increasingly used to treat chronic liver diseases. We previously reported that acupuncture combined with curcumin, a natural antifibrotic compound, could remarkably attenuate liver fibrosis in chemically intoxicated rats, but the underlying molecular mechanisms are poorly understood. The present study was aimed at investigating the effects of acupuncture combined with curcumin on plateletderived growth factor (PDGF) signalling and extracellular matrix (ECM) regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The PDGF transports its signals through PDGF receptors and cascades of mitogenactivated protein kinases (MAPK) downstream, including ERK-MAPK, JNK-MAPK (Jun aminoterminal kinase) and P38-MAPK. Therefore, decreases in PDGF can interrupt this cascade and become an effective agent for the improvement of hepatic fibrosis (20). Similar to the present study, Fu et al (2008) have demonstrated that curcumin significantly decreases expression of PDGF-BB and TGF-β1 genes and consequently protects liver tissues against injuries.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The PDGF transports its signals through PDGF receptors and cascades of mitogenactivated protein kinases (MAPK) downstream, including ERK-MAPK, JNK-MAPK (Jun aminoterminal kinase) and P38-MAPK. Therefore, decreases in PDGF can interrupt this cascade and become an effective agent for the improvement of hepatic fibrosis (20). Similar to the present study, Fu et al (2008) have demonstrated that curcumin significantly decreases expression of PDGF-BB and TGF-β1 genes and consequently protects liver tissues against injuries.…”
Section: Discussionsupporting
confidence: 86%
“…Curcumin may protect liver against oxidative stress resulted from ethanol use (19). Studies have shown that curcumin supplement with acupuncture cause significant decreases in PDGF-BB in rats (20). Regarding effects of curcumin, it has been reported that 8-week use of curcumin causes significant decreases in TGF-β1 gene expression (21).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, curcumin acts on liver injuries by targeting multiple sites, for example platelet-derived growth factor-β receptor (PDGF-βR) [ 301 ], tissue growth factor β (TGFβ) [ 302 , 303 ], toll-like receptors (TLRs) [ 304 ], matrix metalloproteinases (MMPs) [ 301 , 305 ], peroxisome proliferator-activated receptors (PPARc) [ 305 ], apoptotic pathway [ 303 , 306 ] microRNAs [ 307 ], and inflammatory cytokines [ 304 , 305 , 308 , 309 ].…”
Section: The Anti-inflammatory and Anti-oxidative Activities Of Hementioning
confidence: 99%
“…There are many studies proving the effect of curcumin on HSCs, and this has been a potential therapeutic approach to be researched. There are reported evidences that TGFb (Reyes-Gordillo et al, 2008), PDGFRb, serum PDGF, CTGF (Zhang et al, 2012), SMAD2-3 (Yao et al, 2012), TNFa (Tu et al, 2012), matrix metalloproteinases (MMPs) (Morsy et al, 2012), TLRs (Tu et al, 2012), and some inflammatory cytokines (Wu et al, 2010;Bassiouny et al, 2011) are targeted and attenuated.…”
Section: Curcuminmentioning
confidence: 99%